Climate Change will impact Natural Calamities, Socio-Economic activities, Health, Nutrition, Crops, Biodiversity, Costal & Marine Life and Regional Diplomacy in CPEC Region - Malik, Hasan Yaser (Pakistan Business Review, 2025)
Although China Pakistan Economic Corridor was envisaged by former Chinese Prime Minister Zhou Enlai in 1963 as a link to the Middle East market for Chinese product, however was formally announced in 2015. Since its inception, most of the China Pakistan Economic Corridor Phase-1 projects, including electricity, communication infrastructure, Gwadar Port and Gwadar International Airport have been completed, however a phase comprising of social sector development projects is under progress. Focus of future development includes cooperation among industrial, science, technology and agricultural sectors.  Development of Special Economic Zones, oil and natural gas pipelines, Gwadar Port and Main Line-1 Railway Project needs special attention for an early completion. The progress of China Pakistan Economic Corridor, especially being a flagship component of ever-expanding Chinese Belt Road Initiative has emerged as a point of concern for a few Extra Regional and Regional Powers, which are endeavouring to implicate China Pakistan Economic Corridor by creating terrorism-based security scenario in Pakistani coastal Balochistan province. Both Chinese and Pakistani nations are working relentlessly to end the malicious menace of terrorism. Apart from the threat of terrorism, China Pakistan Economic Corridor is also facing the hazardous impacts of climate change in form of cloud bursts, glacier melting and floods due to increasing temperatures. It needs to be analysed by conducting qualitative research by collecting the available information and deducing the fact pragmatically that the hazards of climate change can cause more damage in comparison with terrorism hence there is a need to address such impacts diligently for prudent solutions.
Keywords: Climate change; impact; CPEC; challenges; infrastructure; rising; temperature and terrorism